A Pilot Study of a Computerized Decision Support System to Detect Invasive Fungal Infection in Pediatric Hematology/Oncology Patients. (17th August 2015) - Bartlett, Adam; Goeman, Emma; Vedi, Aditi; Mostaghim, Mona; Trahair, Toby; O'Brien, Tracey A.; Palasanthiran, Pamela; McMullan, Brendan
Abstract : OBJECTIVE: Computerized decision support systems (CDSSs) can provide indication-specific antimicrobial recommendations and approvals as part of hospital antimicrobial stewardship (AMS) programs. The aim of this study was to assess the performance of a CDSS for surveillance of invasive fungal infections (IFIs) in an inpatient hematology/oncology cohort. METHODS: Between November 1, 2012, and October 31, 2013, pediatric hematology/oncology inpatients diagnosed with an IFI were identified through an audit of the CDSS and confirmed by medical record review. The results were compared to hospital diagnostic-related group (DRG) coding for IFI throughout the same period. RESULTS: A total of 83 patients were prescribed systemic antifungals according to the CDSS for the 12-month period. The CDSS correctly identified 19 patients with IFI on medical record review, compared with 10 patients identified by DRG coding, of whom 9 were confirmed to have IFI on medical record review. CONCLUSIONS: CDSS was superior to diagnostic coding in detecting IFI in an inpatient pediatric hematology/oncology cohort. The functionality of CDSS lends itself to inpatient infectious diseases surveillance but depends on prescriber adherence. Infect. Control Hosp. Epidemiol. 2015;36(11):1313–1317